Prevalence study of canine skin tumours in Santa Catarina, Brazil, between 1998 and 2002 (Revista de Ciências Agroveterinárias, 2006)
The purpose of this study was to perform an epidemiological survey of canine cutaneous neoplasms diagnosed in the Animal Pathology Laboratory of CAV/UDESC from 1998 to 2002. The data was obtained from the archives of the laboratory's histopathological reports, and consisted of skin tissue samples from necropsy or submitted by veterinarians who work in the State of Santa Catarina. The information was divided in several categories such as age, sex, breed and city of origin. From the period of 1998 to 2002, 10.935 histopathological reports were performed. From the total amount, 1.065 (9,7%) were skin samples suspected of being neoplastic. Only 13,9% of the suspected samples were diagnosed as non-neoplastic. Among these, the most common were epidermal cysts, dermatitis and granulomas. The remaining 917 cases were diagnosed as tumours, and the most common were the mast cell tumour (13,4%), transmissible venereal tumor (7,5%), sebaceous gland adenoma (7%) and histiocytoma (6,43%). Most of the skin samples (26,7 % of the cases) came from Florianópolis, followed by Joinville with 15,39% . The tumors distribution of between males and females was of 40,13 and 42,87%, respectively, and 17% of the skin samples did not have information about gender. The most affected age group with skin tumors was from 6 to 10 years of age, with 353 cases (38,5%). The mongrels and cross-breds were most affected, followed by the Poodle and Boxer breed groups. Therefore, dermatological problems in small animal medicine have an important role in the veterinary clinician's routine. Of all skin pathologies, tumours represent a large fraction of diagnosis. However, in many cases, the lack of minimal information prevented a better histopathological report and compromises statistical and epidemiological studies.
Keywords: skin tumors; canine; pathology.